Clinical and demographic characteristics predictive of treatment outcomes for certolizumab pegol in moderate to severe Crohn's disease: analyses from the 7‐year PRECiSE 3 study. Issue 3 (1st June 2015) - Sandborn, W. J.; Melmed, G. Y.; McGovern, D. P. B.; Loftus, E. V.; Choi, J. M.; Cho, J. H.; Abraham, B.; Gutierrez, A.; Lichtenstein, G.; Lee, S. D.; Randall, C. W.; Schwartz, D. A.; et al.
SUMMARY Background Clinical factors were previously identified as predictors of short‐term treatment efficacy in Crohn's disease (CD). The PRECiSE 3 (P3) 7‐year trial provides an opportunity to study predictors of short‐ and long‐term clinical remission among CD patients treated with certolizumab pegol (CZP). Aim To identify factors that influence long‐term remission of CD with CZP treatment. Methods Patients who had completed placebo‐controlled studies (PRECiSE 1/PRECiSE 2, P1/P2) enrolled in P3 and received open‐label CZP 400 mg every 4 weeks up to 7 years. Baseline predictors included, but were not limited to, smoking status, disease duration, prior inflammatory bowel disease (IBD) surgery, Harvey–Bradshaw Index (HBI), albumin, haematocrit and CZP exposure; association with time to initial remission (HBI ≤4) was tested for patients who received CZP in P1/P2; time to loss of remission/frequency of maintenance of remission was also tested. Univariate analyses and multivariate Cox or logistic regression models were used. Results Predictors for initial remission (N = 377) included age, haematocrit, prior IBD surgery and entry HBI (P < 0.05 for all). Predictors for loss of remission (N = 437) included HBI, serum albumin concentration, haematocrit, smoking status and exposure. Predictors of maintenance of remission (N = 437) included haematocrit, IBD surgery, HBI, disease duration, serum albumin concentration and exposure. Significant predictors were confirmed with stepwise multivariate regression models. Conclusions These analyses identified several influential parameters for short‐and long‐term remission of Crohn's disease with certolizumab pegol treatment. The data yield valuable hypotheses regarding factors that influence certolizumab pegol treatment. More investigation is needed. (ClinicalTrials.gov identifier NCT00552058).